Galectin-3 negatively regulates the frequency and function of CD4+CD25+Foxp3+ regulatory T cells and influences the course of Leishmania major infection - Fermino, Marise L. (2013)
Galectin-3, an endogenous glycan-binding protein, plays essential roles during microbial infection by modulating innate and adaptive immunity. However, the role of galectin-3 within the CD4+CD25+Foxp3+ T regulatory (TREG) cell compartment has not yet been explored. Here, we found, in a model of Leishmania major infection, that galectin-3 deficiency increases the frequency of peripheral TREG cells both in draining lymph nodes (LNs) and sites of infection. These observations correlated with an increased severity of the disease, as shown by increased footpad swelling and parasite burden. Galectin-3-deficient (Lgals3−/−) TREG cells displayed higher CD103 expression, showed greater suppressive capacity, and synthesized higher amounts of IL-10 compared with their wild-type (WT) counterpart. Furthermore, both TREG cells and T effector (TEFF) cells from Lgals3−/− mice showed higher expression of Notch1 and the Notch target gene Hes-1. Interestingly, Notch signaling components were also altered in both TREG and TEFF cells from uninfected Lgals3−/− mice. Thus, endogenous galectin-3 regulates the frequency and function of CD4+CD25+Foxp3+ TREG cells and alters the course of L. major infection.